Bagaimana Peranan Kualitas Jasa terhadap Loyalitas Pelanggan pada Sektor Penerbangan di Indonesia? - Nicholas Wilson; Jessica Jessica (Business Management Journal, 2020)
This study was conducted in order to determine whether or not service quality plays a significant role in affecting customer loyalty toward an airline in the Indonesian aviation industry. This study implements quantitative-survey method, in which questionnaires were utilized as the instruments used to collect all of the data required for the completion of this study. A total of 250 respondents participated in this study, in which, Respondents should be Indonesians who’ve boarded an Indonesian full-service carrier at least twice (for return trips) between August 2019 to July 2020. All of the questionnaires were electronically distributed to the respondents, and since all of the questionnaires were filled properly, then it could be concluded that the response rate of this study is 100%. After further analyses and assessments, authors would like to conclude that all of the data had been properly and completely filled by all of the respondents, thus enabling all of the data to be further analyzed in this study, in which, the results of the data analyses will be used as the basis on whether or not to reject or support the hypotheses posited in this study. All of the data were analyzed using PLS-SEM method. After analyzing all of the data, authors would like to conclude that service quality plays a significant role in affecting customer or passengers’ loyalty toward an Indonesian full-service carrier. Furthermore, out of 5 (five) factors which form or act as the dimensions of service quality, responsiveness turns out to be the dimension which had the strongest effect in explaining variable service quality in this study.